The marketing of the small enterprise - Zajfertová, Alena; Štědroň, Bohumír, 1948-; Šubrt, Vít; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
The purpose of this thesis is to analyse the marketing of a small enterprise, and it's position and importance on the market. It will also include an analysis of the informational and financial support of the EU. For the practical part there was chosen a small enterprise Nana Vogue, which is specialised in luxurious clothing.
Vedoucí práce: Bohumír Štědroň
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: podniková ekonomika a management [obor bakal. práce]; marketing; bakalářské práce; marketing; bachelor's theses